Duration of prior psychotic illness and clozapine response: a retrospective observational study using electronic health records. (June 2022) - Jones, Rowena; Upthegrove, Rachel; Price, Malcolm J.; Pritchard, Megan; Chandan, Joht Singh; Legge, Sophie; MacCabe, James H.
Background: Clozapine is the gold-standard medication for treatment-resistant schizophrenia (TRS) yet its initiation is often delayed. Objective: To examine whether earlier initiation of clozapine in TRS is associated with lower Clinical Global Impression – Severity (CGI-S) scores at 2 years. Methods: This was a retrospective cohort study from electronic health records of patients with first adequate trial of clozapine at the South London and Maudsley mental health service between 1 January 2007 and 31 December 2016. Dates of illness onset and clozapine commencement were manually extracted from anonymised case notes. CGI-S scores were rated blind to illness duration. Ordinal logistic regression was used to describe the association between illness duration at baseline and CGI-S outcome score at 2 years, following adjustment for CGI-S start score and other key covariates. Results: Among the 401 patients included, there was an association between illness duration and CGI-S outcome score with a 4% increase in the odds of a higher (worse) outcome CGI-S score per year of illness [adjusted odds ratio (AOR) = 1.04; 95% confidence interval (CI): 1.01–1.06]. The association between illness duration and clozapine response was most marked at less than 4 years illness duration. There were too few clozapine initiations within the first 2 years of illness to draw any conclusions about early clozapine initiation. Conclusion: Initiation of clozapine within 2–4 years of psychotic illness onset offers the best outcome for TRS, but the advantage, if any, of earlier initiation is unclear from these data.